Polypropylene nonwoven cloth fresh-keeping material with synergistic antibacterial and ethylene scavenging functions and preparation method thereof

CN122879987APending Publication Date: 2026-10-09WUYI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611019804.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-09
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

紫外接枝法虽能实现稳定的抗菌性能,但该方法设备投入高、工艺复杂、反应条件苛刻(需紫外光、光引发剂和惰性气体保护),难以进行大规模工业化推广

Benefits of technology

本发明提供的聚丙烯非织造布保鲜材料,以聚丙烯非织造布为基材,在其表面形成包含聚乙烯醇(PVA)、脱氢乙酸钠(SD)和二氧化钛(TiO2)的复合涂层。其中,PVA作为成膜基质和亲水组分,其分子链上密集的羟基(OH)赋予材料良好的亲水性和吸湿性,能够有效吸收包装内的多余水分,避免表面结露,同时为后续功能组分提供附着位点。脱氢乙酸钠作为广谱抗菌剂,能够有效抑制包装内微生物的生长繁殖,防止果蔬腐败。二氧化钛不仅作为光催化抗菌剂,增强材料的抗菌性能,更重要的是其具有优异的乙烯清除能力,能够催化降解果蔬释放的乙烯气体,从而延缓果蔬的后熟和衰老进程。三者通过湿度管理、抗菌抑菌、乙烯清除的多重协同机制,克服了单一功能改性的缺陷,全面提升了保鲜效果。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122879987A_ABST
    Figure CN122879987A_ABST
Patent Text Reader

Abstract

The application provides a polypropylene non-woven fabric fresh-keeping material with synergistic antibacterial and ethylene scavenging functions and a preparation method thereof. The fresh-keeping material comprises a polypropylene non-woven fabric substrate and a composite coating coated on the surface of the substrate, and the composite coating comprises polyvinyl alcohol, sodium dehydroacetate and titanium dioxide. The application also provides a preparation method and application of the fresh-keeping material. The fresh-keeping material realizes the synergistic effect of hydrophilic moisturizing, broad-spectrum antibacterial and ethylene catalytic degradation, can effectively control the humidity in the package, inhibit the breeding of microorganisms and delay the post-harvest ripening process of fruits and vegetables, thereby significantly prolonging the shelf life of fruits and vegetables at room temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of functionalized textile materials and active food packaging technology, specifically relating to a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions and its preparation method. Background Technology

[0002] Polypropylene (PP) nonwoven fabric is widely regarded as an ideal substrate for active packaging of fruits and vegetables due to its good mechanical properties, excellent air permeability, and significant cost advantages. However, PP material has low intrinsic surface energy, exhibits strong hydrophobicity (static water contact angle is typically >110°), and lacks any inherent antibacterial and preservative activities. This makes it unable to effectively regulate the humidity environment inside the packaging, easily leading to condensation on the inner wall of the packaging, thereby accelerating microbial growth. At the same time, it cannot inhibit the post-harvest ripening process of fruits and vegetables (such as softening and discoloration caused by ethylene), severely limiting its direct application in the preservation of perishable fruits and vegetables with high humidity, such as strawberries and mulberry leaves.

[0003] To improve the performance of PP nonwoven fabrics, existing technologies mainly employ UV grafting or impregnation coating methods for functional modification. While UV grafting can achieve stable antibacterial properties, this method requires high equipment investment, complex processes, and stringent reaction conditions (requiring UV light, photoinitiators, and inert gas protection), making large-scale industrial application difficult. Conventional impregnation coating methods often use single antibacterial agents (such as chitosan, plant essential oils, or silver ions). These methods have several drawbacks, such as rapid initial release leading to short-lasting preservation effects and insufficient efficacy in the later stages; weak adhesion between functional components and the substrate, resulting in easy coating peeling. More importantly, existing technologies often neglect the synergistic effect between humidity management within the packaging, microbial inhibition, and ethylene removal, leading to limited actual preservation effects.

[0004] Therefore, developing a PP nonwoven fabric preservation material that simultaneously possesses good hydrophilicity, antibacterial properties, ethylene removal ability, and water retention properties, and establishing a simple, cost-controllable, and easily industrialized preparation method to solve at least one of the above-mentioned problems in the existing technology, has significant practical significance and market value. Summary of the Invention

[0005] The present invention aims to at least solve one of the aforementioned technical problems existing in the prior art. To this end, the present invention provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions. This preservation material achieves a synergistic effect of hydrophilic moisturizing, broad-spectrum antibacterial, and ethylene catalytic degradation by forming a composite coating comprising polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide on the surface of the polypropylene nonwoven fabric. This effectively regulates humidity within the packaging, inhibits microbial growth, and slows down the ripening process of fruits and vegetables, thereby significantly extending the shelf life of fruits and vegetables at room temperature.

[0006] This invention also provides a method for preparing polypropylene nonwoven fabric preservation material that is simple in process, cost-controllable, and easy to industrialize.

[0007] This invention also provides the application of polypropylene nonwoven fabric preservation material in fruit and vegetable preservation.

[0008] The first aspect of the present invention provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions.

[0009] A first aspect of the present invention provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, the polypropylene nonwoven fabric preservation material comprising: Polypropylene nonwoven fabric substrate; and A composite coating is applied to at least one surface of the polypropylene nonwoven fabric substrate; The slurry forming the composite coating comprises polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide.

[0010] The polypropylene nonwoven fabric preservation material of the present invention, which has synergistic antibacterial and ethylene removal functions, has at least the following beneficial effects: The polypropylene nonwoven fabric preservation material provided by this invention uses polypropylene nonwoven fabric as a substrate, and forms a composite coating on its surface comprising polyvinyl alcohol (PVA), sodium dehydroacetate (SD), and titanium dioxide (TiO2). PVA serves as the film-forming matrix and hydrophilic component, and its molecular chains contain densely packed hydroxyl groups (…). (OH) imparts excellent hydrophilicity and hygroscopicity to the material, effectively absorbing excess moisture within the packaging and preventing surface condensation, while also providing attachment sites for subsequent functional components. Sodium dehydroacetate, as a broad-spectrum antibacterial agent, effectively inhibits the growth and reproduction of microorganisms within the packaging, preventing fruit and vegetable spoilage. Titanium dioxide not only acts as a photocatalytic antibacterial agent, enhancing the material's antibacterial properties, but more importantly, it possesses excellent ethylene scavenging capabilities, catalytically degrading ethylene gas released by fruits and vegetables, thereby delaying the ripening and senescence process. Through a multi-faceted synergistic mechanism of humidity management, antibacterial inhibition, and ethylene scavenging, these three components overcome the shortcomings of single-function modification, comprehensively improving the preservation effect.

[0011] According to some embodiments of the present invention, in the slurry forming the composite coating, the mass ratio of the polyvinyl alcohol, the sodium dehydroacetate, and the titanium dioxide is 15:4.5:(5~15).

[0012] By optimizing the ratio of the three components, a preservation material with a uniform coating structure and stable performance can be obtained. Experiments show that within this addition range, the material achieves the best balance of hydrophilicity, antibacterial properties, and ethylene removal ability, resulting in optimal preservation effect. When the amount of titanium dioxide added is too low, the ethylene removal and photocatalytic antibacterial effects are insufficient; when the amount added is too high, the nanoparticles tend to agglomerate, increasing the brittleness of the coating and negatively impacting performance.

[0013] According to some embodiments of the present invention, the amount of titanium dioxide added accounts for 4%-8% of the total mass of the composite coating.

[0014] When the amount of titanium dioxide added is too low, the ethylene removal and photocatalytic antibacterial effects are insufficient; when the amount added is too high, the nanoparticles tend to agglomerate, increasing the brittleness of the coating and negatively impacting performance. Therefore, the optimal mass ratio range ensures the best overall performance.

[0015] According to some embodiments of the present invention, the slurry forming the composite coating further includes a dispersant and / or a plasticizer.

[0016] According to some embodiments of the present invention, the dispersant is sodium hexametaphosphate.

[0017] According to some embodiments of the present invention, the plasticizer is glycerin.

[0018] Sodium hexametaphosphate, as a dispersant, can effectively adsorb onto the surface of nano-titanium dioxide particles. Through steric hindrance and electrostatic repulsion, it prevents TiO2 nanoparticles from flocculating and settling in the slurry, improving its suspension stability and thus ensuring the uniform distribution of functional components in the coating. Glycerin, as a plasticizer, can increase the flexibility of PVA molecular chains, improve the film-forming properties and toughness of the coating, and prevent the coating from cracking.

[0019] According to some embodiments of the present invention, the mass of the sodium hexametaphosphate is 25% to 35% of the mass of the titanium dioxide.

[0020] According to some embodiments of the present invention, the slurry for forming the composite coating, based on 100 mL of water, comprises: 15 g polyvinyl alcohol, 4.5 g sodium dehydroacetate, 6.83 g-14.46 g titanium dioxide, 2.05 g-4.34 g sodium hexametaphosphate, 2.38 mL glycerol, and 50 mL ethanol. This specific formulation of the slurry loads the functional components onto the substrate, resulting in a simple and easily controllable process. The addition of ethanol helps reduce the surface tension of the slurry, improving its wettability and penetration into the hydrophobic polypropylene substrate, thereby enhancing the adhesion between the coating and the substrate.

[0021] According to some embodiments of the present invention, the preservation material has an asymmetric structure, wherein the inner surface in contact with fruits and vegetables is a hydrophilic surface and the outer surface is a hydrophobic surface.

[0022] According to some embodiments of the present invention, the outer surface is coated with a hydrophobic layer.

[0023] According to some embodiments of the present invention, the hydrophobic layer is formed of an organosilicon hydrophobic agent.

[0024] This asymmetrical design allows the inner layer (hydrophilic layer) to absorb moisture from the transpiration of fruits and vegetables, maintaining suitable humidity inside the bag; while the outer layer (hydrophobic layer) prevents external moisture from entering, maintaining the overall barrier properties of the packaging and avoiding the humidity imbalance problem caused by a single hydrophilic coating. Furthermore, the hydrophobic layer is inexpensive, simple to manufacture, and easy to implement.

[0025] A second aspect of the present invention provides a method for preparing the polypropylene nonwoven fabric preservation material of the first aspect of the present invention, comprising the following steps: S100, the polypropylene nonwoven fabric substrate is pretreated to obtain a pretreated substrate; S200, the components of the slurry forming the composite coating are dispersed in a solvent to form a slurry; S300, the slurry is coated onto the surface of the pretreated substrate and dried to obtain the polypropylene nonwoven fabric preservation material.

[0026] The preparation method of the present invention uses conventional impregnation. Coating The drying process does not require expensive UV grafting equipment or complex chemical reaction control. The reaction conditions are mild (atmospheric pressure and low temperature), and the raw materials are all commercially available bulk industrial products. The production cost is low, the process is short, and the operation is convenient, making it very suitable for large-scale industrial production.

[0027] According to some embodiments of the present invention, step S200 includes: (1) Add polyvinyl alcohol to water at 80±2℃ and stir until completely dissolved to obtain the first solution; (2) After cooling the first solution to room temperature, add sodium dehydroacetate and glycerol, and stir until dissolved to obtain the second solution; (3) Add sodium hexametaphosphate dispersant to the second solution, stir evenly, then add titanium dioxide, and sonicate to obtain the third solution; (4) Add ethanol to the third solution, stir evenly and degas by ultrasonication to obtain the slurry.

[0028] This step-by-step preparation method ensures thorough and uniform mixing of all components. In particular, dissolving PVA first, followed by cooling and then adding SD avoids the impact of high temperatures on SD stability. Adding SHMP before TiO2 ensures preferential adsorption of the dispersant onto the particle surface, achieving optimal dispersion. Ultrasonic treatment is an effective physical means of dispersing nanoparticles; combined with the chemical dispersing effect of SHMP, it ensures long-term stable suspension of TiO2 in the slurry.

[0029] According to some embodiments of the present invention, after step S300, the method further includes: A hydrophobic layer is coated on the outer surface of the polypropylene nonwoven fabric preservation material, and the hydrophobic layer is formed by an organosilicon hydrophobic agent. This allows for the simple construction of an asymmetric structure preservation material that is hydrophilic on the inside and hydrophobic on the outside, further enhancing its preservation performance.

[0030] The third aspect of the present invention provides the application of the polypropylene nonwoven fabric preservation material of the first aspect of the present invention or the polypropylene nonwoven fabric preservation material prepared by the method of the second aspect of the present invention in the preservation of fruits and vegetables.

[0031] This polypropylene nonwoven fabric preservation material performs exceptionally well in the room-temperature preservation of perishable fruits and vegetables such as strawberries and mulberry leaves. Application examples show that strawberries packaged with this material, after 6 days of storage at room temperature (25±2℃), exhibited a weight loss rate of only 19.56%, significantly lower than those packaged with unmodified polypropylene fabric (which rotted on the 3rd day) and commercially available comparison bags (which rotted on the 5th day). Furthermore, the fruit remained bright red, without rotting or mold, and retained its edible value. This demonstrates that this material can effectively extend the room-temperature shelf life of fruits and vegetables, and has broad application prospects in e-commerce logistics for fresh produce and home cold storage. Attached Figure Description

[0032] Figure 1 These are Fourier transform infrared (FTIR) spectra of PP nonwoven fabric preservation materials modified with different amounts of TiO2.

[0033] Figure 2 These are the microscopic morphologies of PP raw fabric magnified at different magnifications, where (a) is magnified 100 times, (b) is magnified 200 times, and (c) is magnified 1000 times.

[0034] Figure 3 These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 100 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0035] Figure 4These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 200 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0036] Figure 5 These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 1000 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0037] Figure 6 It is one of the side view profile diagrams of the static water contact angle on the surface of each sample.

[0038] Figure 7 This is the second side view of the static water contact angle profile of each sample surface.

[0039] Figure 8 These are actual photos of strawberries stored at room temperature for 6 days under different packaging treatments.

[0040] Figure 9 This is a graph showing the change in weight loss rate of strawberries during storage under different packaging treatments.

[0041] Figure 10 These are actual photos of mulberry leaves stored on the 3rd day under different packaging treatments. Detailed Implementation

[0042] The following will describe the concept and technical effects of the present invention clearly and completely with reference to embodiments, so as to fully understand the purpose, features and effects of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are all within the scope of protection of the present invention.

[0043] In the description of this invention, the terms "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., refer to specific features, structures, materials, or characteristics described in connection with that embodiment or example, which are included in at least one embodiment or example of the invention. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0044] Unless otherwise specified, "room temperature" in this invention means 25℃±5℃.

[0045] Unless otherwise specified, "about" in this invention means that the allowable error is within ±2%.

[0046] Unless otherwise specified in the examples, the procedures should be performed under standard conditions or conditions recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available products.

[0047] In this embodiment, the method for preparing the slurry forming the composite coating is as follows: Measure 100 mL of deionized water into a beaker and place the beaker in a 63°C constant temperature water bath. Weigh 15 g of PVA. After the temperature stabilizes, add the weighed polyvinyl alcohol to the beaker and stir continuously to allow it to swell at a constant temperature. Measure 35 mL of anhydrous ethanol into the beaker and add it to continue swelling. Weigh 4.5 g of SD and the required weight of titanium dioxide according to the corresponding mass fraction.

[0048] The solutions containing (0, 6.83, 8.66, 10.54, 12.47, 14.46) and sodium hexametaphosphate (0, 2.05, 2.60, 3.16, 3.74, 4.34) were mixed until the solution became viscous and flocculent with no solid particles. The solution was then cooled to room temperature in a water bath, and sodium dehydroacetate was added and stirred until completely dissolved. Sodium hexametaphosphate (SHMP) was added as a dispersant to prevent TiO2 flocculation and precipitation, improving its suspension stability in the finishing solution. After stirring evenly, TiO2 was added to dissolve the solution. The solution was then sonicated at 38°C for 30 minutes. Then, 2.38 mL of glycerol (a plasticizer) and 15 mL of anhydrous ethanol were added and stirred for 15 minutes. Finally, the solution was sonicated again to remove air bubbles, yielding the antibacterial finishing solution. A total of 50 mL of anhydrous ethanol was actually added.

[0049] Example 1 This embodiment provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, which contains 4 wt% TiO2.

[0050] The mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide is 15:4.5:6.83.

[0051] (1) Composite finishing solution formula: PVA 15g, deionized water 100mL, anhydrous ethanol 35mL, SD 4.5g, glycerol 2.38mL, SHMP 2.05g, TiO2 6.83g.

[0052] (2) Preparation method: PP nonwoven fabric (purchased from Guangzhou Junqi Nonwoven Fabric Co., Ltd., density 45g / m³) was used. 2Cut to 148mm×210mm, soak in anhydrous ethanol for 24 hours, rinse with deionized water, and dry at 60℃ for later use.

[0053] In a 63°C water bath, PVA was added to a mixture of deionized water and anhydrous ethanol and stirred until completely dissolved. After cooling to room temperature, SD and glycerol were added, followed by SHMP and stirring until homogeneous. Then TiO2 was added and ultrasonically treated at 38°C for 30 minutes with stirring until homogeneous. Ultrasonic degassing was performed for 20 minutes to obtain the finishing solution.

[0054] Pretreated PP nonwoven fabric was fixed on a flat surface, and antibacterial finishing liquid was evenly coated onto the sample surface using a coating brush, followed by three coats with a glass rod. The sample was then dried in an 80℃ constant temperature forced-air drying oven, and after cooling to room temperature, the coating and drying steps were repeated to obtain a single-sided double-layer coated antibacterial PP packaging material, denoted as PVA / SD / 4%TiO2-PP.

[0055] (3) Performance testing: Contact angle (3s): 81.86°; air permeability: 2.217 mm / s. Weight loss of strawberries on day 5 of preservation: 20.03%.

[0056] It should be noted that in this invention: The contact angle was tested using the seated drop method with a contact angle meter (HYK-Z-103). 2 μL of deionized water was used as the test solution. Data was collected uniformly at 3 seconds of water droplet contact, and the average value of five different locations was taken for each sample. Results are as follows: Figure 2 As shown, the contact angle of the original PP nonwoven fabric was approximately 115°; the contact angle of the 0% TiO2 group decreased to 57.64°; with the increase of TiO2 addition, the contact angle further decreased, reaching 51.53° in the 6% TiO2 group, and then leveled off. This indicates that the addition of TiO2 effectively enhanced the surface polarity of the coating.

[0057] The air permeability test was conducted using the pressure difference method with an air permeability tester (YG461E-III) covering a test area of ​​20 cm². 2 The pressure difference was 100 Pa, the temperature was 23 °C, and the relative humidity was 50%. Each sample was tested 3 times and the average value was taken.

[0058] The weight loss rate was determined by placing commercially available fresh strawberries and sweet peas into separate food storage bags for each experimental group and control group, with three parallel samples per group. The samples were stored at room temperature (approximately 25°C) for 5 days, and the weight was measured and the weight loss rate was calculated daily.

[0059] Example 2 This embodiment provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, which contains 5 wt% TiO2.

[0060] The mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide is 15:4.5:8.66.

[0061] (1) Composite finishing solution formulation: Based on Example 1, add 8.66g of TiO2 and 2.60g of SHMP.

[0062] (2) Preparation method: Same as in Example 1.

[0063] (3) Performance testing: Contact angle (3s): 77.82°; air permeability: 1.836 mm / s. Weight loss rate of strawberries on day 5 of preservation: 21.22%.

[0064] Example 3 This embodiment provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, which contains 6 wt% TiO2.

[0065] The mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide is 15:4.5:10.54.

[0066] (1) Composite finishing solution formulation: Based on Example 1, add 10.54g of TiO2 and 3.16g of SHMP.

[0067] (2) Preparation method: Same as in Example 1.

[0068] (3) Performance testing: Contact angle (3s): 67.49°; air permeability: 1.522 mm / s. Weight loss of strawberries on day 5 of preservation: 21.79%.

[0069] Example 4 This embodiment provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, which contains 7wt% TiO2.

[0070] The mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide is 15:4.5:12.47.

[0071] (1) Composite finishing solution formulation: Based on Example 1, 12.47g of TiO2 and 3.74g of SHMP were added.

[0072] (2) Preparation method: Same as in Example 1.

[0073] (3) Performance testing: Contact angle (3s): 61.16°; air permeability: 1.415mm / s. Weight loss rate of strawberries on day 5 of preservation: 21.07%.

[0074] Example 5 This embodiment provides a polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, which contains 8wt% TiO2.

[0075] The mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide is 15:4.5:14.46.

[0076] (1) Composite finishing solution formulation: Based on Example 1, 14.46g of TiO2 and 4.34g of SHMP were added.

[0077] (2) Preparation method: Same as in Example 1.

[0078] (3) Structural characterization: FT-IR display, at 400-600cm - The Ti-O-Ti peak intensity is highest at ¹, and the -OH stretching vibration peak increases from 3342 cm⁻¹. - ¹Redshifted to 3328cm - ¹, The broadened peak shape indicates a strong hydrogen bond interaction between TiO2 and PVA. SEM shows that the fiber surface is uniformly covered by a dense composite coating, with relatively uniform distribution of TiO2 particles and a small amount of local agglomeration.

[0079] (4) Performance testing: Contact angle (3s): 65.68°, (5s): 60.54°; air permeability: 1.247mm / s.

[0080] (5) Strawberry preservation effect: After 6 days of storage at room temperature, the fruit remained bright red, with some fruits retaining white, unripe areas on their surface. Dissection of the pulp revealed that the white pulp was the most abundant component. The fruit maintained good firmness and showed no signs of rot or mold. On day 6, the overall sensory score was 26 out of 30, the highest among the experimental group. On day 5, the weight loss rate was 19.56%, the lowest among the experimental group.

[0081] (6) Observation on the preservation of mulberry leaves: The material has a good water retention effect on mulberry leaves (weight loss rate of 35.71% on the 3rd day, which is better than the low TiO2 group and the original cloth group), but obvious browning occurs. This is related to TiO2 catalysis and the activation of polyphenol oxidase by the weakly alkaline microenvironment, indicating that when used for leafy vegetables, the outer layer structure needs to be optimized or compounded with anti-browning agents.

[0082] Example 6 This embodiment provides a food preservation material with an asymmetric structure.

[0083] Based on the double-layer hydrophilic coating prepared in Example 5, a 0.5wt% organosilicon hydrophobic agent solution is coated on the outer surface of the preservation material (the surface that does not contact fruits and vegetables), and dried and cured at 80°C to obtain an asymmetric structure preservation material with an inner layer of hydrophilic moisture absorption / antibacterial and an outer layer of hydrophobic barrier.

[0084] Commercially available silicone hydrophobic agents can be used.

[0085] Comparative Example 1 This comparative example uses untreated PP nonwoven fabric purchased from Guangzhou Junqi Nonwoven Fabric Co., Ltd.

[0086] Contact angle: 116.48° (hydrophobic). Strawberry preservation: Obvious mold spots appear on the surface on the 3rd day, the fruit softens severely, and it loses its edible value after a weight loss of 15.47%.

[0087] Comparative Example 2 This comparative example uses commercially available HDPE cling film.

[0088] It has excellent water retention but almost zero air permeability. Strawberry preservation: By the 4th day, an off-odor appears, the surface softens, and a large amount of condensation forms inside the packaging, accelerating spoilage.

[0089] Comparative Example 3 This comparative example uses commercially available Dingyuxian zippered fruit and vegetable preservation bags (green).

[0090] The inner surface is superhydrophilic (contact angle 0°), and the outer surface is hydrophobic. Mulberry leaves have good water retention (weight loss rate of 6.93% on the 3rd day), but strawberries showed obvious rotting and fruit deformation after storage for 4-5 days, and their preservation effect was inferior to that of Example 5 of this invention.

[0091] Comparative Example 4 This comparative example provides a control sample (0% TiO2) preservation material and its preparation method.

[0092] (1) Composite finishing solution formula: PVA 15g, deionized water 100mL, anhydrous ethanol 35mL, SD 4.5g, glycerol 2.38mL, SHMP 0g, TiO2 0g.

[0093] (2) Preparation method: Cut the PP nonwoven fabric into 148mm×210mm pieces, soak them in anhydrous ethanol for 24 hours, rinse them with deionized water, and dry them at 60℃ for later use.

[0094] In a 63°C water bath, PVA was added to a mixture of deionized water and anhydrous ethanol and stirred until completely dissolved. After cooling to room temperature, SD and glycerol were added and stirred until homogeneous. The mixture was then ultrasonically degassed for 20 minutes to obtain the finishing solution.

[0095] Pretreated PP nonwoven fabric was fixed on a flat surface, and antibacterial finishing liquid was evenly coated onto the sample surface using a coating brush, followed by three coats with a glass rod. The sample was then dried in an 80℃ constant temperature forced-air drying oven, and after cooling to room temperature, the coating and drying steps were repeated to obtain a single-sided double-layer coated antibacterial PP packaging material, denoted as PVA / SD / 0%TiO2-PP.

[0096] (3) Performance testing: Contact angle (3s): 83.87°; air permeability: 2.849 mm / s (nozzle 0.8 mm). Weight loss of strawberries on day 5: 19.96%.

[0097] Application examples The preservation material prepared in Example 5 was cut into 148mm × 210mm pieces, folded in half, and heat-sealed on both sides to make preservation bags. Fresh strawberries (approximately 20g / bag) were placed inside, sealed, and stored at room temperature (25±2℃). The bags were observed and weighed daily. The results showed that after 6 days of storage, the strawberries had a weight loss rate of only 19.56%, with no rotting, and remained edible. In contrast, commercially available green PP preservation bags began to show mold on the 4th day of storage and severely rotted on the 5th day; the unmodified PP fabric rotted on the 3rd day. The preservation material prepared in this invention significantly extends the shelf life of strawberries at room temperature.

[0098] In the test results of this invention: Figure 1 These are Fourier transform infrared (FTIR) spectra of PP nonwoven fabric preservation materials modified with different amounts of TiO2.

[0099] Observable at 400~600cm -1 A characteristic absorption peak of Ti-O-Ti appears in the range, and the intensity of this characteristic peak gradually increases with the increase of the TiO2 addition ratio; at the same time, the 3342 cm⁻¹ peak corresponding to the hydroxyl group of PVA molecule is observed. -1 The peak wavenumber of the stretching vibration is 3328 cm⁻¹. -1 The red shift and significant broadening of the peak shape indicate that a stable hydrogen bond is formed between the nano-titanium dioxide and the polyvinyl alcohol coating matrix, and TiO2 is successfully incorporated into the coating system. Furthermore, the higher the amount added, the stronger the interaction between the two phases, resulting in a strong bond between the composite coating components.

[0100] Figure 2 These are the microscopic morphologies of PP raw fabric magnified at different magnifications, where (a) is magnified 100 times, (b) is magnified 200 times, and (c) is magnified 1000 times.

[0101] It can be clearly observed that the PP fibers are smooth and clean, without any coating, with loose pores between fibers, no particles adhering to the fiber surface, and the fibers themselves are hydrophobic and smooth without a hydrophilic modification layer. This indicates that the original PP nonwoven fabric is only a simple fiber skeleton, without antibacterial or ethylene removal functional components, and lacks a hydrophilic coating on the surface, making it a blank control substrate for subsequent modified materials.

[0102] Figure 3 These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 100 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0103] Figure 3 Under uniform magnification of 100x, the morphology of six groups of nonwoven fabric fibers modified with different titanium dioxide contents was compared. Compared with the 0wt% sample without TiO2, the fiber surfaces of the 4%~8wt% TiO2 samples were all covered with a continuous composite coating. With the increase of TiO2 addition, the integrity of the coating coverage gradually improved, and the 8wt% group had the most uniform fiber coating with only a small amount of nanoparticles slightly agglomerated. This indicates that the composite slurry can be uniformly coated on the surface of PP fibers, and increasing the TiO2 addition is beneficial to the complete coating of the fibers. Only excessive addition will result in slight agglomeration, and effective surface modification can be achieved in the 4%~8wt% range.

[0104] Figure 4 These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 200 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0105] Figure 4 With the magnification increased to 200x, differences in coating thickness and particle distribution can be more clearly distinguished. The 0wt% sample coating contains only PVA and sodium dehydroacetate, with a smooth surface and no particle protrusions. The 4%~6wt% TiO2 samples have uniformly dispersed particles, resulting in a thin and continuous coating. The 7% and 8wt% samples show increased coating thickness and localized small particle agglomerations. This indicates that low to medium amounts of TiO2 (4%~6%) exhibit the best dispersion within the coating, while high addition amounts (7% and 8%) may cause slight agglomeration, but this does not disrupt the overall continuity of the coating, allowing it to remain stably adhered to the fibers.

[0106] Figure 5These are scanning electron microscope images of samples modified with different amounts of TiO2, magnified 1000 times. Among them, (a) is TiO2 0wt%, (b) is TiO2 4wt%, (c) is TiO2 5wt%, (d) is TiO2 6wt%, (e) is TiO2 7wt%, and (f) is TiO2 8wt%.

[0107] Figure 5 Magnification of 1000x allows for direct observation of the microscopic dispersion of nano-TiO2. Samples without TiO2 show a smooth, particle-free surface. 4%–6 wt% TiO2 nanoparticles are uniformly embedded within the PVA coating without large-scale agglomeration. Samples with 7% and 8 wt% show localized agglomeration of TiO2 particles. This indicates that titanium dioxide additions of 4%–8 wt% can be loaded into the coating, with optimal dispersion below 6 wt%. Above 6 wt%, the agglomeration of nanoparticles intensifies, potentially affecting the coating's uniformity and permeability.

[0108] Figure 6 It is one of the side view profile diagrams of the static water contact angle on the surface of each sample.

[0109] Figure 6 The images show the outlines of water droplets on the inner and outer surfaces of commercial PE food preservation film and commercially available pink / green zipper food preservation bags. The commercially available PE film is hydrophobic on both the inner and outer surfaces, and the water droplets are perfectly spherical. The commercially available green food preservation bag has a completely spread inner surface (superhydrophilic) and the water droplets on the outer surface are closed and hydrophobic. This shows that existing commercially available food preservation packaging simply distinguishes between a hydrophilic inner layer and a hydrophobic outer layer, but lacks antibacterial and ethylene removal functions. It relies solely on humidity control and cannot simultaneously inhibit bacteria and delay the ripening of fruits and vegetables.

[0110] Figure 7 This is the second side view of the static water contact angle profile of each sample surface.

[0111] Figure 7 Comparing the water droplet morphology of PP raw fabric and 0%~8wt% TiO2 modified materials at 3 seconds and 5 seconds: the pure PP raw fabric produced full water droplets with a contact angle exceeding 110°, exhibiting strong hydrophobicity; the 0wt% TiO2 sample showed slightly spread water droplets; as the TiO2 addition increased, the water droplet spread increased continuously, while the contact angle decreased continuously. After 6wt%, the rate of decrease slowed down, and the 8wt% sample showed a contact angle as low as 60.54° at 5 seconds, exhibiting the best hydrophilicity. This indicates that the composite coating can significantly improve the hydrophobicity of PP nonwoven fabric, and the addition of TiO2 can further enhance the hydrophilicity of the material. The 8wt% formulation showed the best moisture absorption and anti-condensation effects.

[0112] Figure 8 These are actual photos of strawberries stored at room temperature for 6 days under different packaging treatments.

[0113] Figure 8The appearance of strawberries after 6 days of storage with 0%, 4%, 5%, 6%, 7%, and 8 wt% TiO2 modified materials is visually presented: The 0% TiO2 group showed softening and slight mold; the 4%–7 wt% groups showed decreased redness and softened flesh; the 8 wt% TiO2 group showed bright color, no mold or rot, and firm flesh, exhibiting the best sensory quality. This indicates that high TiO2 content (8 wt%) (with a mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide of 15:4.5:14.46) synergistically with sodium dehydroacetate provides long-lasting antibacterial effects and catalytic decomposition of ethylene, maximally delaying strawberry aging and decay, and demonstrating significantly better preservation at room temperature than samples with low TiO2 ratios.

[0114] Figure 9 This is a graph showing the change in weight loss rate of strawberries during storage under different packaging treatments.

[0115] Figure 9 The study included the average weight decay curve and weight loss rate change curve of strawberries. In the control group, the pure PP cloth experienced a rapid increase in weight loss and rot after 3 days, while the commercially available preservation bags showed excessive weight loss and rot on the 5th day. The 0% TiO2 modified sample showed moderate weight loss. The 4%~7wt% TiO2 group showed a gradual increase in weight loss. The 8wt% TiO2 experimental group (with a mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide of 15:4.5:14.46) showed the lowest weight loss throughout the entire process, with a weight loss rate of only 19.56% after 6 days of storage.

[0116] At 0% TiO2, PVA exhibits only weak hydrophilic buffering, no sterilization, no ethylene removal, moderate water loss, and moderate weight loss.

[0117] When TiO2 content is 4%~7wt%, the antibacterial and ethylene removal effects continue to strengthen, but the coating pores are gradually blocked, the air permeability continues to decrease, the stuffiness inside the bag exacerbates evaporation and water loss, the air permeability attenuation effect dominates, and the weight loss gradually increases.

[0118] With 8wt% TiO2, the TiO2 filling forms a dense, reversible moisture-absorbing network, achieving the highest dynamic humidity balance capability. Simultaneously, its antibacterial and ethylene removal properties reach peak levels, offsetting the negative impact of low air permeability. This results in minimal moisture loss and spoilage, leading to optimal weight loss throughout the entire process. Therefore, the 8wt% TiO2 formulation (with a mass ratio of polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide of 15:4.5:14.46) exhibits the best hydrophilicity, balancing moisture within the packaging, reducing water transpiration loss from strawberries, inhibiting microbial growth, effectively controlling fruit weight loss, and achieving optimal overall preservation performance.

[0119] Figure 10 These are actual photos of mulberry leaves stored on the 3rd day under different packaging treatments.

[0120] Figure 10Comparing the appearance of mulberry leaves packaged in different materials after 3 days of storage, the mulberry leaves packaged in pure PP cloth showed severe water loss and wilting; commercially available food storage bags retained moisture well but were prone to becoming damp; the modified material of this invention reduced water loss, but the mulberry leaves in the 8wt% TiO2 group showed browning. This indicates that this material is suitable for long-term preservation of berries such as strawberries; when used for leafy vegetables such as mulberry leaves, the TiO2 photocatalytic system activates polyphenol oxidase, inducing browning, requiring the combination of an outer hydrophobic structure or the addition of anti-browning agents to optimize the formulation.

[0121] The present invention has been described in detail above with reference to the embodiments. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention.

Claims

1. A polypropylene nonwoven fabric preservation material with synergistic antibacterial and ethylene removal functions, characterized in that, The polypropylene nonwoven fabric preservation material includes: Polypropylene nonwoven fabric substrate; and A composite coating is applied to at least one surface of the polypropylene nonwoven fabric substrate; The slurry forming the composite coating comprises polyvinyl alcohol, sodium dehydroacetate, and titanium dioxide.

2. The polypropylene nonwoven fabric preservation material according to claim 1, characterized in that, In the slurry forming the composite coating, the mass ratio of the polyvinyl alcohol, the sodium dehydroacetate, and the titanium dioxide is 15:4.5:(5~15).

3. The polypropylene nonwoven fabric preservation material according to claim 1, characterized in that, The amount of titanium dioxide added accounts for 4%-8% of the total mass of the composite coating.

4. The polypropylene nonwoven fabric preservation material according to claim 1, characterized in that, The slurry forming the composite coating further includes a dispersant and / or a plasticizer; and / or, the dispersant is sodium hexametaphosphate; and / or, the plasticizer is glycerol; and / or, the mass of the sodium hexametaphosphate is 25% to 35% of the mass of the titanium dioxide.

5. The polypropylene nonwoven fabric preservation material according to claim 1, characterized in that, Based on 100 mL of water, the slurry forming the composite coating comprises: 15 g polyvinyl alcohol, 4.5 g sodium dehydroacetate, 6.83 g - 14.46 g titanium dioxide, 2.05 g - 4.34 g sodium hexametaphosphate, 2.38 mL glycerol and 50 mL ethanol.

6. The polypropylene nonwoven fabric preservation material according to any one of claims 1 to 5, characterized in that, The polypropylene nonwoven fabric preservation material has an asymmetric structure, with its inner surface in contact with fruits and vegetables being a hydrophilic surface and its outer surface being a hydrophobic surface; and / or, the outer surface is coated with a hydrophobic layer; and / or, the hydrophobic layer is formed by an organosilicon hydrophobic agent.

7. A method for preparing a polypropylene nonwoven fabric preservation material as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S100, the polypropylene nonwoven fabric substrate is pretreated to obtain a pretreated substrate; S200, the components of the slurry forming the composite coating are dispersed in a solvent to form a slurry; S300, the slurry is coated onto the surface of the pretreated substrate and dried to obtain the polypropylene nonwoven fabric preservation material.

8. The method according to claim 7, characterized in that, Step S200 includes: (1) Add polyvinyl alcohol to water at 80±2℃ and stir until completely dissolved to obtain the first solution; (2) After cooling the first solution to room temperature, add sodium dehydroacetate and glycerol, and stir until dissolved to obtain the second solution; (3) Add sodium hexametaphosphate dispersant to the second solution, stir evenly, then add titanium dioxide, and sonicate to obtain the third solution; (4) Add ethanol to the third solution, stir evenly and degas by ultrasonication to obtain the slurry.

9. The method according to claim 7, characterized in that, Following step S300, the method further includes: A hydrophobic layer is coated on the outer surface of the polypropylene nonwoven fabric preservation material, the hydrophobic layer being formed by an organosilicon hydrophobic agent.

10. The application of the polypropylene nonwoven fabric preservation material according to any one of claims 1-6 or the polypropylene nonwoven fabric preservation material prepared by any one of claims 7-9 in the preservation of fruits and vegetables.